Two Sides of the Same Coin: The Good and Bad of Alumni Affiliation during Auditor Evidence Collection - Earley, Christine E.; Kuselias, Stephen G.; MacKenzie, Nikki L. (The Accounting Review, 2024)
ABSTRACT Regulators and researchers express concern about auditors who leave their firms for employment at their clients, due to lingering relationships which might represent a threat to audit quality. These relationships could negatively impact audit quality through undue influences of the client personnel on auditor judgment. We examine how these relationships influence novice auditors during evidence collection. Understanding the effects of alumni affiliation on evidence collection is important because undiscovered issues at this phase may go unaddressed, potentially hurting audit quality. Contrary to most research findings, we find that alumni affiliation can benefit the audit by increasing auditors’ evidence collection. However, we also find, when auditors become depleted, the benefits of alumni affiliation actually reverse, as auditors overrely on the relationship, leading them to prematurely cease evidence collection. These findings have implications for both practitioners and researchers. Data Availability: Data are available from the authors upon request.